Mesoporous Tantalum Oxide Photocatalyst: Structure and Activity Evaluation. Issue 1 (11th January 2017) - Seisenbaeva, Gulaim A.; Cojocaru, Bogdan; Jurca, Bogdan; Tiseanu, Carmen; Nedelec, Jean‐Marie; Kessler, Vadim G.; Parvulescu, Vasile I.
Abstract: Mesoporous nanostructured pure tantalum pentoxide and Eu‐doped Ta2 O5 were produced by facile and reproducible one‐pot procedure not involving structure directing agents. The as‐produced material is poorly crystalline and catalytically inactive. Photoluminescence behavior of the doped oxide indicates that it is formed by quick nucleation of pure Ta2 O5, leaving the Eu‐dopant only on the surface of the formed material. Further thermal treatment leads to crystallization and structural transformation as revealed by in situ X‐Ray Diffraction (XRD) and Rietveld refinement used to identify and quantify the emerging phases as well as Diffuse Reflectance UV‐vis Spectroscopy (DR‐UV‐Vis) and Raman Spectroscopy studies. The thermally induced transformation results in generation of surface oxygen vacancies that provide the material with pronounced photocatalytic activity in selective oxidation of aromatic amine compounds. The processes of generation and curing of the vacancies have been followed and quantified by temperature programmed oxidation and reduction and photoluminescence studies, offering in depth insight into the reaction mechanism. Abstract : Oxidation of 4‐methylbenzyl‐amine on mesoporous Ta2 O5 occurred with the selective formation of the corresponding intermolecular imine. The catalytic behavior of this material has been explained by correlated studies of quenching the oxygen vacancies, photo‐luminescence and reaction kinetics. These results were also well correlated to the XRD and Raman structural characterization.